The Influence of Dislocation Junctions on Accumulation of Dislocations in Strained FCC – Single Crystals; Advanced Materials Research; Vol. 1013 : Structure and Properties of Metals at DifferentEnergy Effects and Treatment Technologies - Starenchenko V. A. Vladimir Aleksandrovich; Cherepanov D. N. Dmitry Nikolaevich; Kurinnaya R.; Zgolich M.; Selivanikova O. V. Olga Valerievna (2014, 2014)
Title screen